2011
DOI: 10.1051/0004-6361/201015490
|View full text |Cite
|
Sign up to set email alerts
|

Detecting planets around very cool dwarfs at near infrared wavelengths with the radial velocity technique

Abstract: Context. Radial velocity monitoring of very cool dwarfs such as late M-and hot L-dwarfs has become a promising tool in the search for rocky planets as well as follow-up planetary candidates around dwarfs detected by transit surveys. These stars are faint at optical wavelengths, as their spectral flux distribution peaks at near-infrared (NIR) wavelengths. For this reason, it is desirable to measure the radial velocities in this wavelength regime. However, in the NIR very few medium-and high-resolution spectrogr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 39 publications
2
29
0
Order By: Relevance
“…Detailed simulations of the photon-limited RV precision in M dwarfs were carried out by Reiners et al (2010); Rodler et al (2011);Bottom et al (2013); Plavchan et al (2015); Figueira et al (2016). With only very few exceptions, these studies relied on synthetic spectra from model atmosphere simulations.…”
Section: Radial Velocity Information Contentmentioning
confidence: 99%
“…Detailed simulations of the photon-limited RV precision in M dwarfs were carried out by Reiners et al (2010); Rodler et al (2011);Bottom et al (2013); Plavchan et al (2015); Figueira et al (2016). With only very few exceptions, these studies relied on synthetic spectra from model atmosphere simulations.…”
Section: Radial Velocity Information Contentmentioning
confidence: 99%
“…Several studies showed that the RV jitter will be divided by at least a factor of 2 due to the lower contrast between the dark spot regions and the quiet photosphere (Marchwinski et al (2015) & Reiners et al (2010; Rodler et al (2011), respectively for Sun-like stars & late M dwarfs). In this context, the new generation of high resolution/precision velocimeters working in the nIR domain (e.g., CARMENES 7 , SPIRou 8 , CRIRES+ 9 ) present a tremendous interest.…”
Section: Photosphere Occupancymentioning
confidence: 99%
“…As result, they found that the highest RV precision for M-dwarfs is attained in the Y-band around 1 μm and not in the J-, H-or K-band. For L-dwarfs, however, Rodler et al (2011) reported that the highest RV precision is attained in the J-band.…”
Section: Resultsmentioning
confidence: 99%
“…We note that and Rodler et al (2011) carried out theoretical RV precision studies of M-and L-dwarfs by adopting theoretical models of M-dwarfs (e.g. del ).…”
Section: Resultsmentioning
confidence: 99%